Kaidah-Kaidah Pemahaman dan Pengambilan Hukum Al-Qur’an dan As-Sunnah (Studi Tentang Lafazh ‘Am, Khash, Lafazh Muthlak dan Muqayyad) - Abdul Wahid (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2015)
Every decision in the Islamic shariah law should be based on the original source, that are nash A1-Qur'an and As-Sunnah as the main source of the Islamic law. The way of law delving from the nash uses the approach of meaning and lafaldz or wording. An overview of the Qur'an to the law does not only use a particular form of sentences, but also in various forms, for instance command sentences (shighat amr), prohibition sentences (shighat nahy), sentences which are characteristically general, muthlaq and so forth. The ushul fiqh scholars make the norms to understand the syara’ nashs and delve the taklify correctly from the nashs, so that they are along with what is meant by the language of the nashs themselves. In making the norms- the scholars was directed by the method which once was used by the Prophet SAW in explaining the laws of the Al-Qur'an and the set of laws texts that had been briefed on the As-Sunnah